Hearing Loss in Acromegaly - A Review - Teixeira, Liane Sousa; Silva, Isabelle Braz de Oliveira; Sampaio, Andre Luiz Lopes; Oliveira, Carlos Augusto Pires de; Bahamad Júnior, Fayez (International Archives of Otorhinolaryngology, 2018)
Introduction Acromegaly is a chronic disease caused by growth hormone (GH) excess due to a GH-secreting pituitary adenoma in most cases. There is reasonable data to presume the possible influence of chronic GH and insulin-like growth factor I (IGF-I) hyperproduction on the anatomical structures involved in normal sound perception, and on its conductive and/or sensorineural part.Objectives To review the literature about acromegaly and hearing loss.Data Synthesis A systematic literature search was performed using the MEDLINE database, including hand-searching reference lists from original articles. The search was performed using the terms hearing loss and acromegaly, and only 5 studies were found.Conclusion The results are not consistent, but led to different conclusions. Therefore, more studies with greater numbers of patients with acromegaly are needed.
Keywords: deafness; acromegaly; hearing loss